2012
DOI: 10.3389/fnhum.2012.00322
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical dysmorphology of the medial superior olivary nucleus in sudden fetal and infant death

Abstract: This study expands our understanding of the organization of the human caudal pons, providing a morphologic characterization of the medial superior olivary nucleus (MSO), component of the superior olivary complex (SOC) that plays an important role in the processing of acoustic information. We examined victims of sudden unexplained fetal and infant death and controls (n = 75), from 25 gestational weeks to 8 months of postnatal age, by complete autopsy and in-depth autonomic nervous system histological examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Information about the location, morphology, function, and developmental defects related to these structures can be found in our previous articles. [54][55][56][57][58][59] Here, we report brief considerations about the most frequent alterations observed in the brain stem of eSIDS, beyond the KFN hypoplasia, that is, the hypoplasia of nuclei of the raphe system and of the arcuate nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Information about the location, morphology, function, and developmental defects related to these structures can be found in our previous articles. [54][55][56][57][58][59] Here, we report brief considerations about the most frequent alterations observed in the brain stem of eSIDS, beyond the KFN hypoplasia, that is, the hypoplasia of nuclei of the raphe system and of the arcuate nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Irregular cytoarchitectural patterns like hypoplasia/agenesis, immature hypercellularity, and dysgenesis of contiguous structures involved in breathing circuit in medial superior olivary nucleus were reported in a study, and it was proposed that this nucleus had influence on all the vital activities along with hearing (45). …”
Section: Brainstem Control Of Respiration During the Transition From mentioning
confidence: 99%
“…Six studies have reported specific findings in the structures of the pons in SIDS [95–100]. Of these, two met the criteria for inclusion [96,97].…”
Section: The Mesencephalonmentioning
confidence: 99%